Iron-Limited Biofilms of Candida albicans and Their Susceptibility to Amphotericin B - Baillie, George S. (American Society for Microbiology (ASM), 1998)
Biofilms of Candida albicans were grown in vitro under iron limitation and at a low growth rate to simulate conditions for implant-associated biofilms in vivo. Their properties were compared with those of glucose-limited biofilms grown under analogous conditions. At steady state, the adherent cell populations of iron-limited biofilms were double those of glucose-limited biofilms, although the growth rates were similar (0.038 to 0.043 h(−1)). Both biofilm types were resistant to amphotericin B, but daughter cells from iron-limited biofilms were significantly more susceptible to the drug than those from glucose-limited biofilms.